Hubungan Tingkat Pengetahuan Diabetes Mellitus Terhadap Kadar Gula Darah Pasien Diabetes Mellitus di Puskesmas X - umul farida; Djembor Sugeng Walujo; Nanda (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Diabetic Mellitus is a chronic disease caused a limited or inneffective insulin produced by pancreas. Diabetes is a big health problems that has reached an worry level and is a global threat. A knowledge has an important role for behavior. This research is used to look a correlation between level of knowledge with of blood sugar levels in patients of diabetic mellitus at the X Health Center. This research used an analytic survey design with a cross-sectional program. The samples was 93 patients with inclusion criteria in the form in patient of diabetic mellitus at the X Health Center and willing to be respondents. This research was held in December 2022 until January 2023. The research used instrument a questionnaire sheet by DKQ 24. The results of the univariate research were obtained by 64,5% of patient had a good levels knowledge and 35,5% had a not good level of knowledge, 60,2% of patient had a normal blood sugar levels and 39,8% of patient had abnormal blood sugar levels. The bivariate with a Chi-Square statistical test found that there a correlation between the level of knowledge with of blood sugar levels in diabetic mellitus patients at the X Health Center in Kediri City with a P value of 0.014. From this research it can be conclude that there a significant correlation between the level knowledge with of blood sugar levels patients of diabetic mellitus at the X Health Center. Hoped the results this research will give information to the X Health Center to continue providing education about diabetes mellitus to patients as a support the stability of the patient's blood sugar levels with a better life.